The Utilization of Augmented Reality Technology for the Development of Tourism Information Media - Maru, Rosmini; Nur, Ali Rahmat Muhammadiyah; Yusuf, Muhammad; Nyompa, Sukri; Rusdi, - (Society of Visual Informatics, 2022)
The industrial revolution 4.0 has brought tourism trends using enriched interactive technology services. Technology in the world of tourism has helped the expansion of the industry through the promotion and mediation of independent tourists to carry out all services and transactions easily, including obtaining tourist information. This study aims to develop promotion media for geography education tourism in Soppeng Regency and test the effectiveness of the media. This study adopted the Alessi & Trollip learning multimedia development model. The developed media was tested on 20 respondents with 10-item usability scale statements and 5 response options ranging from agreeing to strongly disagree. The level of effectiveness of the media developed after being tested using the usability scale (SUS) system is included in the Good category (good) with an average score of 76.5. This level of effectiveness is included in the acceptable to users or acceptable category, with a grade scale of C and an adjective rating in the Good or good category. The results of this study also indicate that users are satisfied with the developed media but are not enthusiastic so that users can switch to other, more interesting media at any time. In the end, based on the final score obtained, it was concluded that the promotion media for geography education tourism in Soppeng Regency (battle city application) was effective and acceptable to users.Â